(untitled) (Research, Society and Development, 2020)
This article propose is to investigate the profile of the students of Brazilian Sign Language at UFC, in the first semester of 2019, discussing issues related mainly to their relationship with sign language and proximity to the deaf community, the reasons that led them to choose the course and your future prospects. It is a cross-sectional descriptive study with quantitative and qualitative approaches. Data collection took place on March 4, 2019 (Phase 1), identifying with the course coordination the list of students enrolled regularly in 2019.1, totaling 104, of which 13 (12.5%) abandoned academic activities or were institutionally enrolled and 91 (87.5%) attended at least one undergraduate course, constituting the sample. In the second phase, a mixed questionnaire was applied at the Federal University of Ceará, from April 10 to June 13, 2019. Descriptive analysis of the data and thematic content analysis were adopted, defining the thematic core: demographic profile ; experience in the deaf community and Brazilian Sign Language; academic education; motivation for choosing the Sign Language as a course and future perspectives. The results pointed to a majority of female students (61.4%), adults (50.6%), listeners (67.5%) and workers (56.6%). The first contact with the deaf community took place in experiences prior to entering the course (66.3%) and, in the majority, the students target is to act as a teacher of Sign Language and attend postgraduate courses in similar areas. More accurate results can be found from complementary research with the student body in its entirety.